Y=2/9x-7

Simple and best practice solution for Y=2/9x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=2/9x-7 equation:


x in (-oo:+oo)

Y = (2/9)*x-7 // - (2/9)*x-7

Y-((2/9)*x)+7 = 0

Y+(-2/9)*x+7 = 0

Y-2/9*x+7 = 0 // - Y+7

-2/9*x = -(Y+7) // : -2/9

x = (-(Y+7))/(-2/9)

x = 9/2*(Y+7)

x = 9/2*(Y+7)

See similar equations:

| 1x+54=7x | | 2=10/3z=3z-7/3 | | 1/16a^2-1/25=0 | | a=8+b | | U=6*8n+6*35+7*n+7*1 | | =6*8n+6*35+7*n+7*1 | | x^2-208=0 | | f(a)=4x^2+2x+8 | | 2n+m-7m=-2 | | 5/6=-1/8x | | 1/3x2-4=21 | | 7x^2+6xy-y^2=0 | | 4(x+6)-3x=-2x+2-8 | | 0.7x-33.33=x+7 | | 11a-b+3a-(-7b)= | | w^2-3w-1890=0 | | 12x^2-(4x-3)(3x+1)=-2 | | 4(x-4)+2x=3(x-2)+5 | | 0.75x-33.3=x+7 | | U=23(6)+240 | | 3x-x=15 | | U=23n+240 | | 6x+9-7x-14=0 | | -3t(t-1)=2t+6 | | 2/2x-5/6x | | U=14n+9n+231+9 | | (8x^5)/(3)-(7x^3)/(6) | | s/616 | | -9h+15=27-2h | | 76-4x=7x-21 | | 6m-7n^5/3m^3*n^3 | | 1/3×21 |

Equations solver categories